2005
DOI: 10.1186/1471-2091-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Water-soluble quinoprotein glucose dehydrogenase (PQQGDH-B) from Acinetobacter calcoaceticus has a great potential for application as a glucose sensor constituent. Because this enzyme shows no activity in its monomeric form, correct quaternary structure is essential for the formation of active enzyme. We have previously reported on the increasing of the stability of PQQGDH-B by preventing the subunit dissociation. Previous studies were based on decreasing the entropy of quaternary structure dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 20 publications
(18 reference statements)
0
26
0
1
Order By: Relevance
“…This result strongly reveals that the signal decline might be caused by loss in PQQ-GDH activity, not by leakage of the enzyme on the electrode. Although this study is desirable for a single-use application, this enzyme stability could be elaborated for the long-term use through genetic engineering, as reported elsewhere [27,28].…”
Section: Resultsmentioning
confidence: 97%
“…This result strongly reveals that the signal decline might be caused by loss in PQQ-GDH activity, not by leakage of the enzyme on the electrode. Although this study is desirable for a single-use application, this enzyme stability could be elaborated for the long-term use through genetic engineering, as reported elsewhere [27,28].…”
Section: Resultsmentioning
confidence: 97%
“…There have also been several reports about the design of FRET-based methods using a GGBP modified with two fluorophores (Ye and Schultz, 2003;Ge et al, 2004) or fused with two different fluorescent proteins, CFP and YFP (Fehr et al, 2003;Deuschle et al, 2005;de Lorimier et al, 2006;Khan et al, 2008), which allow the glucose sensing not only in vitro but also in mammalian cells, as well as the real-time monitoring. We have been engaged in the development of glucose biosensors utilising GGBP as well as engineered enzymes (Igarashi et al, 2004;Okuda and Sode, 2004;Tanaka et al, 2005;Kakehi et al, 2007;Okuda et al, 2007) and recently reported the construction of a GGBP mutant specifically recognising glucose with a higher K d value than that of the wildtype GGBP and demonstrated its potential use in the measurement of physiological glucose concentrations (Sakaguchi-Mikami et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…PQQGDH-B was by the same group improved significantly in thermal resistance (Ser231Lys or Ser415Cys substitution) [69,70] and in catalytic efficiency (Glu277Lys) [71]. A further interesting approach was to increase the stability of PQQGDH-B by introducing a hydrophobic interaction in the dimeric interface (Asn340 was substituted to Phe and the Tyr418 to Phe/Ile) which increased the thermal stability at 55 8C [60]. For the LDA two regions at the border to the active site were mutated by site directed mutagenesis to harbor substrates with elongated hydrophobic side chains.…”
Section: Amino Acid Substitutions At the Active-site And Close Proximitymentioning
confidence: 98%